La posibilidad de conciliación en los procesos de contravenciones de violencia intrafamiliar y la estabilidad familiar. - Guizado Arteaga, Joselyn Anabel (2023)
The administrators of justice in the processes of contraventions of violence against women or members of the family nucleus take as a reference the exclusion to the conciliation established in the Comprehensive Criminal Organic Code in the crimes of this matter to prohibit a conciliation between the procedural subjects; without considering that, in the absence of conciliation, not only is this fundamental right recognized in the Constitution of the Republic of Ecuador violated; but also family stability is threatened, considering that without family there is no society. Conciliation is not an adversarial mechanism, which implies that the parties do not confront each other in their claims, but instead seek a solution to their conflict through dialogue in the case of processes of contraventions of violence against women or members of the family nucleus, the possibility of conciliation would protect family stability, complying with the provisions of the Constitution of the Republic of Ecuador, regarding the obligation of the State to protect the family as the fundamental nucleus of society and guarantee conditions that fully favor the achievement of their fines.